1992
DOI: 10.2149/tmh1973.20.149
|View full text |Cite
|
Sign up to set email alerts
|

A seroepidemiological study of dengue and Japanese encephalitis virus infections in Vientiane, Lao PDR.

Abstract: A total of 141 serum specimens from inhabitants in eight age groups in Vientiane, Lao PDR was examined to estimate the neutralizing anitibody levels to dengue (DEN) and Japanese encephalitis (JE) viruses. From the analyses of the results of neutralization (N) tests, the following conclusions were drawn about the prevalences of DEN and JE viruses in Vientiane: (1) The percentage incidences of N antibodies to DEN 1-4 viruses increased with age, but the incidences of N antibodies to DEN-3 and DEN-4 were lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
1
5
1
Order By: Relevance
“…anti‐dengue IgM positive) were more frequent (126 cases, 3.5%) than JE infections (78 cases, 2.1%). This result confirms and extends previous findings of Bounlu et al (1992) and Fukunaga et al (1993). In addition, our results suggest possible differences in the spatial distribution of recent dengue and JEV infections within Vientiane city.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…anti‐dengue IgM positive) were more frequent (126 cases, 3.5%) than JE infections (78 cases, 2.1%). This result confirms and extends previous findings of Bounlu et al (1992) and Fukunaga et al (1993). In addition, our results suggest possible differences in the spatial distribution of recent dengue and JEV infections within Vientiane city.…”
Section: Discussionsupporting
confidence: 94%
“…The IgG seroprevalence of Vientiane adults aged >35 years (84.6%) was similar to past prevalence estimates of 86.4% (78/94) in Attapeu province in 2001 (Peyerl‐Hoffmann et al 2004). Interestingly, our estimates of IgG seroprevalence among children (9.4%) are lower than those reported by Bounlu et al (1992) and Fukunaga et al (1993). However, given the differences in study design, inferences regarding changes in flavivirus transmission intensity based on these studies alone are not warranted.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…A review of reported JE prevalence in humans in Lao PDR has identified ranges between 0% and 11% in a hospital-based survey in Vientiane of children 15 years of age and under. 70 Other hospital-based surveys in the country have found seroprevalences of up to 75% in Khammouane province, 7% in Luang Namtha, and 4% in Salavan province. 18 Various community level surveys have also found a range of seroprevalences, including 10% and 80% in Khammouane province and Vientiane Municipality, respectively, 71 , 72 and 2.1% in a large-scale serosurvey in Vientiane city.…”
Section: Resultsmentioning
confidence: 95%
“…In 1985 and 1987, large outbreaks of dengue fever (DF) I dengue hemorrhagic fever (DHF) occurred in the urban areas of the Vientiane municipality. In these outbreaks, 1076 and 5232 DF/DHF hospitalized cases were reported to the Vientiane Municipality Health Service, respectively (Bounlu et al, 1992;Fukunaga et al, 1993) . From 1988 to 1993, DF/DHF epidemic did not occur, though several sporadic cases were reported in these areas.…”
Section: Introductionmentioning
confidence: 99%